Management theory and practice - Cole, Gerald A. (South - Western Cengage Learning, 2011)
This classic textbook provides an accessible and authoritative introduction to the whole subject of management, both in theory and in practice. Now in its seventh edition, the text includes new case studies, an updated glossary and a wide range of additional pedagogical features designed to support learning and encourage reflective thinking.